Implantação e monitoramento preliminar de microbacia hidrográfica rural no Sudoeste do Paraná - Battisti, Fernando (2020)
Hydrological monitoring in watershed is a very important technique to understand the water basin's response to rainfall events, acting on the characteristics of the basin's natural formation and the management carried out by man. Improper soil management leads to erosion problems of different magnitudes, causing soil degradation. The erosion carried by water through runoff may reach rivers, causing several other environmental problems. The present study implemented the monitoring system for precipitation, flow and sediment concentration in a hydrographic basin with a total area of 61.81 ha located in the experimental area of UTFPR, in Dois Vizinhos, southwest region of the state of Paraná. The implementation of the monitoring system was completed in May 2019. The monitoring of rainfall events, between May 2019 and February 2020, precipitation, flow and concentration of suspended sediments were monitored during large-scale rainfall events, accounting for two significant rainfall-flow events. Topographic characterization of the basin and physical-hydric soil was also carried out. This information was used to assist in the understanding of the basin's water response to rainfall in its different land uses and management systems. The results showed that in the monitored events less than 5% of the precipitated volume was converted into flow in the basin's exutory. These results may show greater variation, depending on the volume and intensity of precipitation, the antecedent moisture of the soil, the current condition of land use and even the water retention capacity in depreciation areas. The continuous monitoring of this basin over time will represent its performance in relation to other environmental conditions and thus present from the worst to the best level of retention and loss of water and sediment.